2017
DOI: 10.1016/j.ejphar.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of the PI3K inhibitor ZSTK474 on multidrug efflux pumps in resistant cancer cells

Abstract: ZSTK474 is a potent phosphoinositide 3-kinase (PI3K) inhibitor that reduces cell proliferation via G-arrest. However, there is little information on the susceptibility of this anticancer drug to resistance conferred by the multidrug pumps P-glycoprotein (ABCB1) and ABCG2. We have demonstrated that ZSTK474 generated cytotoxicity in cells over-expressing either pump with potency similar to that in drug sensitive cells. In addition, the co-administration of ZSTK474 with the cytotoxic anti-cancer drugs vinblastine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…In addition, the reversal effect of PI3K/AKT signaling pathway inhibitors on MDR mediated by ABCB1 and/or ABCG2 in cancer cells has also been described. It was reported that through the inhibition of the PI3K/AKT signaling pathway, ZSTK474 inhibited the drug transport function and downregulated the protein expression of ABCB1 and ABCG2 [92], whereas PI103 [93], perifosine [94], and LY294002 [95] downregulated ABCB1 expression in sarcoma, breast cancer, and gastric cancer cells, respectively. The PI3K/mTOR dual inhibitor dactolisib reversed MDR mediated by ABCB1 and ABCG2 in multidrug-resistant acute myeloid leukemia (AML) cells [96] and mesothelioma cell lines [97], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the reversal effect of PI3K/AKT signaling pathway inhibitors on MDR mediated by ABCB1 and/or ABCG2 in cancer cells has also been described. It was reported that through the inhibition of the PI3K/AKT signaling pathway, ZSTK474 inhibited the drug transport function and downregulated the protein expression of ABCB1 and ABCG2 [92], whereas PI103 [93], perifosine [94], and LY294002 [95] downregulated ABCB1 expression in sarcoma, breast cancer, and gastric cancer cells, respectively. The PI3K/mTOR dual inhibitor dactolisib reversed MDR mediated by ABCB1 and ABCG2 in multidrug-resistant acute myeloid leukemia (AML) cells [96] and mesothelioma cell lines [97], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The calcein-AM assay to measure the transport function of P-gp was based on previously published methods. , MCF-7 WT and NCI/Adr RES cells were seeded into 96-well tissue-culture plates at a density of 2 × 10 3 cells per well in 100 μL and allowed to adhere for 2 days at 37 °C with 5% CO 2 . Following incubation, the medium was aspirated and cells were washed with PBS and resuspended in 100 μL Hank’s buffered salt solution (HBSS).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro experiments have shown that it can inhibit the proliferation of tumor cells through interfering cell G0/1 stage arrest 42 , 43 . It is exciting that ZSTK474 induced the degradation of multidrug efflux pumps ABCB1 and ABCG2 so as not to be affected by the efflux effect of resistant cancer cells 44 . Furthermore, ZSTK474 exhibited antiangiogenic activity via downregulating HIF-1α and VEGF, and suppressed renal cancer growth in a xenograft model 45 .…”
Section: Discussionmentioning
confidence: 99%